AICCRA support enables West and Central African planning for effectively managing crop pest and disease outbreaks - Segnon, Alcade; Zougmore, Robert (2025)
Responding to CORAF demand, AICCRA technical support and capacity development on foresight analysis has enabled co-developing the Regional Plan for Preparedness and Response to Pest and Disease Outbreaks in West and Central Africa. Launched jointly by the Economic Community of both West and Central African States (ECOWAS and ECCAS), the Plan will strengthen agricultural resilience by anticipating and swiftly responding to disease and pest outbreaks that affect regional food systems.